Upaya Peningkatan Kemampuan Pemahaman Konsep Mahasiswa pada Mata Kuliah Sistem Digital - Rini Widia Putri Z; Purni Munah Hartuti (SAP (Susunan Artikel Pendidikan), 2019)
The purpose of this study is to examine and examine whether the use of modules in digital systems courses can improve students' understanding of concept skills. The population in this study was R2X class students who took digital systems courses in the even semester of the 2018/2019 school year at the Unindra Informatics study program. This research is in the form of classroom action research in two cycles to improve students' understanding of concept skills in digital systems courses using modules. Each cycle goes through stages: 1) Planning, 2) Implementation of actions, 3) Evaluation, 4) Reflection. The instruments in this study were observation sheets and student exercises. Observation results show that the use of modules in lectures can facilitate students in increasing their conceptual understanding abilities. The curves of each activity indicator to facilitate students in improving conceptual abilities are always rising. While the average results of understanding students' concepts increase each cycle of action.